Electrochemiluminescence Determination of a Specific Sequence of the BCR/ABL Gene Related to Chronic Myelogenous Leukemia with a Ferrocene-Labelled Molecular Beacon and a Gold Nanoparticle (AuNP)-Luminol-Silica Nanocomposite. (22nd January 2022) - Li, Yue; Ding, Zhifang; Bao, Ying; Han, Kexin; Li, Guixin
Abstract: A signal-off electrochemiluminescence (ECL) biosensor was developed for the determination of specific sequence of BCR/ABL gene related to chronic myelogenous leukemia based on a mesoporous gold nanoparticle (AuNP)-luminol-silica nanocomposite and the catalytic effect of ferrocene on luminol ECL. Luminol and silica were electrodeposited on the electrode surface and AuNP was deposited on the luminol-silica hybrid film to form the AuNP-luminol-silica nanocomposite film. The AuNP-luminol-silica nanocomposite on the surface provided stable ECL. Ferrocene labeled molecular beacon (Fc-MB) was assembled onto the surface of AuNP-luminol-silica nanocomposite through Au–S bond. After the hybridization of molecular beacon with target DNA, the opening of the stem of Fc-MB caused ferrocene to be away from the electrode surface, which resulted in the decrease of ECL intensity. Accordingly, a signal-off ECL DNA biosensor was developed based on the linear relationship between the reduced ECL intensity and the concentration of the target DNA. Under the selected conditions, the ECL intensity decreased linearly with the logarithm of the concentration of target DNA from 1.0 × 10 −15 to 1.0 × 10 −9 mol/L with a detection limit of 4.6 × 10 −16 mol/L.